PT. Usaha Loka - Andhara Karinda Astadevi; Jessica Suryawan; Joanne Christiana; Made Arrynda N. F.; Maria Adi Widya (Journal of the Community Development in Asia (JCDA), 2018)
One of Indonesian biggest source is wood, so we decided to choose wood furniture as our product to be export. Indonesia has a really good quality of wood, and supported by the good quality of human resources. Therefore, they can produce furniture that is highly competitive with good quality and high art. We collaborate with PT. Usaha Loka to find out about export in the field of furniture. PT Usaha Loka is a company engaged in furniture which is located in Malang. PT. Usaha Loka business has started the furniture business since 1990. They have been running an export business in furniture to a number of countries, namely Singapore, Japan, Germany and etc. There are some products that they sell such as wood flooring and garden furniture that made from wood. We make visits to observe how the procedures for exporting, the documents needed, the costs needed, the flowchart start from the beginning of the production until the goods are exported in the destination country. We also propose two new product ideas, they are 3 in 1 furniture (is a furniture that have chair, table, and drawer which is combined into one) and doors). Key words: furniture, wood, export